The Cost of Female Citizenship: How Price Controls Gendered Democracy in Revolutionary France. - JARVIS, KATIE L. (French Historical Studies, 2018)
In 1793, the National Convention passed two hallmarks of Jacobin legislation: sweeping price controls called the General Maximum and a ban on women's political clubs. At the center of both issues were factional clashes among the Montagnards, Girondins, and Enragés, on the one hand, and Parisian market women called the Dames des Halles and the leading women's club called the Société des Citoyennes Républicaines Révolutionnaires, on the other. Montagnard deputies pointed to marketplace brawls between the Dames and the club women to argue that women were irrational and had no place in formal politics. Consequently, the dominant historiographical narrative frames their ban as codifying Rousseauian gender norms and ideologically stunting women's citizenship at the outset of French democracy. However, this article analyzes the mechanics of the Maximum to argue that the ban on women's clubs emerged from contests over price controls, market regulation, and the economic dimensions of citizenship itself.